Pakistan : Reinvigorating the Trade Agenda - Reis, José Guilherme; Taglioni, Daria (World Bank, Washington, DC, 2014)
This paper reviews Pakistan's recent trade performance, its trade policy and trade costs. Different dimensions of trade performance growth and orientation, diversification and sophistication are assessed, complemented by an in-depth analysis of export dynamics in the period 2001-10 using firm-level data. An econometric exercise is also performed to identify the impact of tariffs, exchange rates, fixed costs to export, foreign demand, and preferential trade policy on the ability of firms to increase their exports. The analysis of Pakistan's trade policy includes tariffs, effective protection and trade restrictiveness estimates, as well as an assessment of the role of preferential trade agreements in the context of regional integration. Finally, the main characteristics of trade facilitation and logistics are analyzed, covering the capacity, performance, quality of services and degree of integration of the logistics system.